One new species of Imitomyia Townsend and five newly recorded species of Dexiinae (Diptera: Tachinidae) from China - Li, Junjian; Li, Yue; Nie, Xutong; Zhang, Chuntian (Zootaxa, 2024)
During our study of the Chinese Fauna of Diptera, many specimens from the subfamily Dexiinae were examined. One new species was recognized, Imitomyia wangi sp. nov. Additionally, five species, Actinochaetopteryx patellipalpis Richter, Chetoptilia puella (Rondani), Leptothelaira longicaudata Mesnil & Shima, Phyllomya takanoi Mesnil and Rutilia (Chrysorutilia) rubriceps Macquart, are newly recorded in China. Their descriptions, illustration and diagnoses are given.